Hubungan Antara Persepsi Siswa Terhadap Kompetensi Guru dan Interaksi Edukatif Guru-Siswa dengan Prestasi Belajar Matematika Siswa Kelas XI SMA N 1 Teras Boyolali - Utomo, Budi; Lilik, Salmah; Agustin, Rin Widya (Jurnal Ilmiah Psikologi Candrajiwa, 2012)
ABSTRACT THE RELATIONSHIP OF THE STUDENTâS PERCEPTION ON TEACHER COMPETENCY AND TEACHER-STUDENT EDUCATIVE INTERACTION TO THE MATHEMATICS LEARNING ACHIEVEMENT OF XI GRADERS OF SMA N 1 TERAS BOYOLALI Budi Utomo Sebelas Maret University The objective of learning mathematics is to grow the structuring of reason or logical thinking ability and positive attitude of students that are useful in studying science and in the application of mathematics in everyday life, but in fact students of mathematics is seen as adaunting subject, resulting in student achievement is low. Therefore it is necessary to seek changes in the process of learning math fun is a top priority so as to improve student math achievement The objective of research is to find out whether there is or not relationship of the studentâs perception on teacher competency and teacher-student educative interaction to the mathematics learning achievement, relationship of the studentâs perception on teacher competency to the mathematics learning achievement, and relationship of the teacher-student educative interaction to the mathematics learning achievement. This research employed a descriptive quantitative method using correlational study approach. The population of research was the XI graders of SMA N 1 Teras Boyolali in the school year of 2010/2011, consisting of 234 students. The sample was taken using cluster random sampling, consisting of 76 students. Techniques of collecting data used were scale for the studentâs perception on teacher competency and the teacher-student educative interaction variables, and documentation for mathematics learning achievement variable. Method of collecting data used was a multiple linear regression analysis and Pearson Product Moment correlation helped by SPSS computer program for MS Windows version 13. Considering the result of data analysis, it can be found Fregression = 50.485 wit p < 0.05. It shows the significant result, meaning that the studentâs perception on teacher competency and the teacher-student educative interaction simultaneously have significant relation to the learning achievement. ResultÂ Â Â Â Â  rx1y = 0.762 with p < 0.05 means that there is a significant relationship between the studentâs perception on teacher competency and the mathematics learning achievement, while rx2y = 0.164 with p < 0,05 means that there is a significant relationship between the teacher-student educative interaction and the mathematics learning achievement. The effective contribution given by studentâs perception on teacher competency and teacher-student educative interaction predictors to the mathematics learning achievement is R = 0.58 or 58%. Â  Keywords: studentâs perception on teacher competency, teacher-student educative interaction, mathematics learning achievement Â